The true blue scouts of Sugar Man Swamp [compact disc, unabridged] - Appelt, Kathi, 1954- (Simon & Schuster Audio, 2013)
'Raccoon brothers Bingo and J'miah are the newest recruits of the Official Sugar Man Swamp Scouts. The opportunity to serve the Sugar Man, the massive creature who delights in delicious sugar cane and magnanimously rules over the swamp, is an honor, and also a big responsibility, since the rest of the swamp critters rely heavily on the intel of these hardworking Scouts. Now it's up to the Scouts to save the swamp from attack by not only hogs, but developers as well"--Container.